Thermal state of steel structures with a combined fire protection system under conditions of fire exposure - Novak, Serhii; Drizhd, Varvara; Dobrostan, Oleksandr (Eastern-European Journal of Enterprise Technologies, 2020)
Given the need to minimize the weight-dimensional indicators of steel structures, the issue of the effective use of a combined fire protection system is relevant. The article deals with the thermal state of steel structures with such a system of fire protection under conditions of fire exposure in the standard temperature mode according to DSTU B V. 1.1-4-98*. The experimental samples used square steel plates with a side of 500 mm and a thickness of 5 mm and 10 mm. The conducted research revealed the peculiarities of dependences of the temperatures of steel structures with passive and reactive fire-retardant materials of two brands on the duration of fire exposure. It was established that these dependences for steel structures with combined, passive, and reactive fire protection systems have a monotonously growing character. The maximum values of the duration of fire exposure are typical of the experimental samples that have the steel plate of the thickness of 10 mm, for a critical temperature of steel of 600 °C. They are 111 min, 101 min, 55 minutes, respectively, for the combined, passive, and reactive fire protection systems. It was established that a combined fire protection system is characterized by an increase in the duration of reaching the critical temperature of steel in comparison with passive and reactive fire protection systems. This is due to the effective combination of physical and chemical properties of passive and reactive fire-retardant materials. For the duration of fire exposure up to 79 min, the value of the duration of reaching the critical temperature of steel for a combined fire protection system exceeds the sum of durations of its achievement, which are typical for passive and reactive fire protection systems. This indicates the effectiveness of a combined system in this range of fire exposure duration. At an increase in the duration of fire exposure, the effectiveness of a combined fire protection system decreases.